In vitro evaluation of the enhancement of glass ionomer cement features by using chitosan and nanodiamond - Silva, Murilo Henrique Torres Da [UNESP]; Strazzi-sahyon, Henrico Badaoui [UNESP]; Gallo, Renata [UNESP]; Fagundes, Ticiane Cestari [UNESP]; Briso, André Luiz Fraga [UNESP]; Perchyonok, Victoria Tamara; Santos, Paulo Henrique Dos [UNESP] (Fundação Odontológica de Ribeirão Preto, 2025)
This study investigated the influence of chitosan and nanodiamond incorporation on the surface, optical, and mechanical properties of glass ionomer cement. Total 56 samples (5 mm diameter and 2 mm thickness) were prepared and divided into 4 groups according to the incorporation of chitosan and nanodiamond on Fuji II glass ionomer cement: Control group: no incorporation; 10%CH group: incorporation of 10% chitosan; 10%ND group: incorporation of 10% of nanodiamond; 5%CH-5%ND group: incorporation of 5% chitosan and 5% nanodiamond (n=14). Analyses of color stability, surface roughness, fluorescence intensity, microhardness, morphology, and chemical composition were investigated. Additionally, water sorption, hygroscopic expansion, contact angle, surface free energy, and total free energy of interaction were also assessed. After the initial readings, the samples were individually stored in red wine solution for 28 days. Data were subjected to ANOVA followed by Tukey´s test (α=.05). Aging in wine solution altered the optical, mechanical, and surface properties of glass ionomer cement regardless of the incorporation of the compound (P<.05). 10% chitosan-incorporated glass ionomer cement promoted higher color alteration, surface roughness, and water sorption after aging (P<.05). 10% nanodiamond-incorporated glass ionomer cement showed higher microhardness compared to the other groups before aging (P<.05), however there were no differences among them after aging (P>.05). In general, no differences between the 5% chitosan- and 5% nanodiamond-incorporated glass ionomer cement and control groups were noted on the evaluated analyses (P>.05). Thus, the incorporation of 5% chitosan and 5% nanodiamond is a satisfactory alternative for maintain the surface, optical, and mechanical properties of the glass ionomer cement.

Este estudo investigou a influência da incorporação de quitosana e nanodiamante nas propriedades de superfície, ópticas e mecânicas de um cimento de ionômero de vidro. Um total de 56 amostras (diâmetro de 5 mm e espessura de 2 mm) foram preparadas e divididas em 4 grupos experimentais de acordo com a incorporação de quitosana e nanodiamante no cimento de ionômero de vidro Fuji II: Grupo Controle: sem incorporação; Grupo 10%CH: incorporação de 10% de quitosana; Grupo 10%ND: incorporação de 10% de nanodiamante; Grupo 5%CH-5%ND: incorporação de 5% de quitosana e 5% de nanodiamante (n=14). Análises de estabilidade de cor, rugosidade de superfície, intensidade de fluorescência, microdureza, morfologia e composição química foram investigadas. Além disso, a sorção de água, expansão higroscópica, ângulo de contato, energia livre de superfície e energia livre total de interação também foram avaliados. Após as leituras iniciais, as amostras foram armazenadas individualmente em solução de vinho tinto por 28 dias. Os dados foram submetidos à ANOVA seguida pelo teste de Tukey (α=.05). O envelhecimento na solução de vinho alterou as propriedades ópticas, mecânicas e de superfície do cimento de ionômero de vidro independentemente da incorporação dos compostos (P<.05). O cimento de ionômero de vidro incorporado com 10% de quitosana promoveu maior alteração de cor, rugosidade de superfície e sorção de água após o envelhecimento (P<.05). O cimento de ionômero de vidro incorporado com 10% de nanodiamante apresentou maior microdureza em comparação com os outros grupos antes do envelhecimento (P<.05), no entanto, não houve diferenças entre eles após o envelhecimento (P>.05). Em geral, não foram observadas diferenças entre os grupos de cimento de ionômero de vidro incorporado com 5% de quitosana e 5% de nanodiamante e os grupos controle nas análises avaliadas (P>.05). Assim, a incorporação de 5% de quitosana e 5% de nanodiamante é uma alternativa satisfatória para manter as propriedades de superfície, ópticas e mecânicas do cimento de ionômero de vidro.
Keywords: chitosan; glass ionomer cement; hardness; nanodiamond; surface properties